2017
DOI: 10.1016/j.amjmed.2016.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Tele-Ultrasound to Guide Management of a Patient with Circulatory Shock

Abstract: of ultrasound supervision independent of the time of day or night. On the system level, this provides a more standardized and supervised foundation on which to base ultrasoundguided management decisions that can significantly affect patient outcomes. On a provider level, it ensures that medical trainees and physician extenders can feel more confident in their technical image acquisition and image interpretation skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…[4] Moreover, 5G enables predictive maintenance scheduling by analyzing real-time equipment performance data, identifying potential issues before they escalate into costly failures, and optimizing maintenance schedules to minimize downtime and maximize operational efficiency. [12] Adopting 5G-enabled facility management solutions offers significant cost savings and operational efficiencies for healthcare facilities. By leveraging real-time data analytics and predictive maintenance capabilities, facilities can reduce maintenance costs, extend equipment lifespan, and minimize unplanned downtime.…”
Section: Improvements In Facility Managementmentioning
confidence: 99%
See 3 more Smart Citations
“…[4] Moreover, 5G enables predictive maintenance scheduling by analyzing real-time equipment performance data, identifying potential issues before they escalate into costly failures, and optimizing maintenance schedules to minimize downtime and maximize operational efficiency. [12] Adopting 5G-enabled facility management solutions offers significant cost savings and operational efficiencies for healthcare facilities. By leveraging real-time data analytics and predictive maintenance capabilities, facilities can reduce maintenance costs, extend equipment lifespan, and minimize unplanned downtime.…”
Section: Improvements In Facility Managementmentioning
confidence: 99%
“…Unauthorized access to this data could lead to identity theft, medical fraud, and breaches of patient confidentiality, eroding trust between patients and healthcare providers. [12] However, ensuring patient privacy and data security in a 5G-enabled healthcare ecosystem presents unique challenges. With the proliferation of connected devices and the rapid exchange of data over high-speed networks, the risk of data breaches and cyberattacks increases exponentially.…”
Section: Patient Privacy and Data Securitymentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, there are no precise data regarding protocols, acquisition time, or image interpretation for telesonography, nor regarding its relevance in changing medical practice ( 4 ) . Some case reports have shown that telesonography provides benefits in the standardized assessment of cardiac function in patients with shock ( 5 ) .…”
Section: Introductionmentioning
confidence: 99%